An Examination of Mine Blasting Accidents Over a Quarter of a Century - H. C. Verakis (International Society of Explosives Engineers, 2006)
This paper summarizes blasting accident data for over a quarter of a century (1978-2004) for all types of surface and underground mining operations in the United States. Although many billions of pounds of explosives and blasting agent have been used by the mining industry, the accident safety record has improved significantly in the past 25 years. Over the past decade, approximately 5 billion pounds of explosives and blasting agents were used annually in the United States. Coal mining has been and continues to be the dominant user of blasting agents.